Phenomenology of violence in digital space and policy response - Matić Bošković, Marina; Kostić, Jelena (Sociološki pregled, 2025)
Digital violence is an increasingly pervasive form of abuse, facilitated through social media, messaging platforms, and online forums. This article explores the causes and phenomenology of digital violence, highlighting psychological, social, and structural drivers, as well as its diverse manifestations, from cyberstalking and image-based abuse to data manipulation and gender-based online harassment. Particular focus is placed on its disproportionate impact on women and girls, and the reinforcement of structural inequalities in digital spaces. This article situates digital violence in global, European, and Serbian context, addressing legal frameworks and policy responses, EU legislation and national initiatives such as Serbia’s “Čuvam te” platform. The authors call for comprehensive, victim-centred approaches that combines legal reform, digital literacy, institutional accountability, and cross-sectoral cooperation.
Keywords: digital violence; digital literacy; structural inequality; victims